ANALISIS MODEL DAN POLA E-GOVERNMENT DI DISTRIK ABEPURA - Muliadi Anangkota (POLITICO, 2022)
Penelitian ini dilatarbelakangi pemikiran bahwa saat ini e-government menjadi salah satu inovasi kebijakan yang diterapkan oleh pemerintahan. Baik pada level pusat maupun daerah. Provinsi Papua telah menerapkan E-Government sejak tahun 2017. Namun, penerapan E-government tersebut belum tersentuh hingga ke tingkat Distrik. Padahal, Distrik sebagai salah satu organisasi pemerintah yang menjalankan fungsi pelayanan maka mau tidak mau harus menerapkan e-government. Penelitian dilakukan di kantor Distrik Abepura. Menggunakan pendekatan deskriptif kualitatif. Hasil Penelitian Menunjukkan bahwa Distrik Abepura telah menerapkan e-government. Model e-government yang ideal untuk diterapkan dalam pelayanan berbasis online di Distrik Abepura adalah model Catalouging, Transaction, Vertical Integration dan Horizontal Integration. Sedangkan pola E-Government yang ideal di terapkan di Distrik Abepura adalah Pola G2C (Government to Citizien). Sedangkan Faktor-Faktor yang mempengaruhi penerapan model dan pola E-Government di Distrik Abepura terdiri dari Faktor Pendukung dan Penghambat. Pada Faktor Pendukung meliputi Komitmen kepala Distrik, Fasilitas Distrik dan Letak Distrik. Sedangkan faktor yang menghambat adalah Sumber Daya Manusia, Penganggaran, Respon Masyarakat, Domain Belum resmi. Kata kunci: pengembangan, Model, Pola, Pemerintahan Elektronik, Distrik  ABSTRACT (11pt Bold Italic)Abstract: This article is the result of research on involving and accessing official access to district / city government offices in the Papua province in supporting the implementation of e-governmnet. The main issues discussed are about the development of implementation of the implementation of e-government in Papua and what factors influence the implementation of e-government in Papua. This research is included in descriptive qualitative research. The data source used is secondary and primary data, namely the study of literature, articles, journals and sites on the internet relating to research conducted. While the primary data used comes from the results of interviews with informant stakeholders. Data collection is done through literature studies, district / city observation websites in Papua, and interviews with Diskominfo in Papua province. The results showed that, as many as 26 district / municipal governments from 29 districts / cities in Papua province had official sites with the go.id domain. Of the 26 web sites all have met indicators, namely access, interaction, transaction and transformation. Several challenges issued by each district / city government in Papua in the development of e-government are factors that support internet support facilities and HR factors that focus on uploading website content. The factor of ignorance of the community about the approval of the official local government site, is also a priority in improving public services through e-government.